Data supporting 'Bioengineering remediation of former industrial sites contaminated with chemical mixtures' - Atai, Emmanuel; Pawlett, Mark; Coulon, Frederic (Cranfield University, 2023)
Research data for a 120-day incubation study to determine the effects and influence of rice husk and wheat straw biochar, as well as spent mushroom compost, on the fate and behaviour of hydrocarbons and metals, as well as their influence on soil microbial communities in a genuinely contaminated former gasworks soil. Specifically, the data included are the changes in alkanes and PAH, metals (total and bioavailable distribution and partitioning), PLFA, Respiration, Microtox, and the respective statistics outputs including anova, principal component analysis and correlation (presented as draftsman charts)
Keywords: biochar'; 'spent mushroom compost'; 'legacy site'; 'bioamendment'; 'bioavailability studies'; 'hydrocarbon'; 'metals'; 'microbial community'